Empathy and prosocial behavior in the work of Juan Rulfo: the stories of failed rescue - Kehila, Ofek (Cartaphilus, 2025)
This article examines the interplay between empathy and prosocial behavior in the works of Mexican author Juan Rulfo (1917–1986); specifically, it examines how the lack of empathy and altruistic motivation shapes the nature of rescue behavior in three stories from The Plain in Flames (1953): “Tell Them Not to Kill Me!” “You Don’t Hear Dogs Barking,” and “Talpa.” The common threads running through these works allow them to be studied as a trilogy that will be referred to here as “The Stories of Failed Rescue.” These stories will be analyzed through the prism of empathy, prosocial behavior, and the interrelation between the two topics. This analysis will provide a unifying interpretation of the works, highlight their essential similarities, and allow to read them together as a statement about human nature and human relations.